Cytokine profile in patients with Parkinson's disease on the background of the autoimmune pathology - Cheboraka, Tetiana; Slobodin, Tatyana; Holovchenko, Yurii; Lisyanyi, Nikolay (ScienceRise: Medical Science, 2018)
Parkinson's disease (PВ) is a chronic, slowly progressing neurodegenerative disease characterized by pathological damage to dopaminergic (DA) neurons, the formation of intraplasmic inclusions, known as Lewy bodies. The etiology of PВ is not completely known, various factors, including genetic, immunological, ecological, initiate the neurodegenerative process of DA-neurons. The results of several clinical studies show the possible role of the immune system, in particular autoimmune mechanisms, in the etiopathogenesis of PD. About 30 years have passed since the first time when activated microglia of the brain was detected on autopsy in patients with PD. Since then, scientists are trying to investigate the effect of the inflammatory process on the development and progression of degeneration of DA-neurons. Aim of the study. To study the concentration of anti-inflammatory (IL-10) and pro-inflammatory cytokines (IL-1β, IL-6) in patients with PD and autoimmune thyroiditis (AIT), to evaluate their connection to motor and non-motor disorders. Materials and methods of research. 109 patients with PD at the age of 47 to 75 years (mean age 61.0±14.0) were examined. The main group consisted of patients of ІА and ІB subgroups, control group of ІІА and IIB subgroups. A general clinical and neurological examination, an evaluation of motor functions using the unified PD scores (UPDRS), neuropsychological testing (MoCA, FAB, BeDI depression scale (BDI), Hamilton anxiety scale (HARS)), a scale for evaluating vegetative disorders in patients with PD. The concentration of cytokines in the blood serum was determined by the method of solid-phase enzyme-linked immunosorbent assay with the help of sets of reagents from Vector Best Ltd. Statistical analysis was done with the use of the program "Statistica 6.0". Results. The study showed a statistically significant increase in the level of proinflammatory cytokines (IL-1β, IL-6) in the blood serum in patients with PD and AIT in comparison with PD patients. The level of anti-inflammatory cytokine IL-10 in the patients of the ІА subgroup was statistically significantly higher in comparison with the patients of the IIA subgroup. We did not find a statistically significant difference between the indices of IL-10 concentration in the serum of patients in the ІB and IIB subgroups. A connection was established at a statistically significant level between the cytokine profile and neuropsychological testing data, the general index of the vegetative assessment scale in patients with PD, the initial scale of the UPDRS scale. Conclusions. Patients with PD and AIT had higher indices of interleukins (IL-1β, IL-6, IL-10) in the blood serum compared with the control group (PD patients). There was a correlation at a statistically significant level between the cytokine profile and motor and non-motor PD manifestations